The Advantages of Using Quipper School as a Media for English Teaching in Junior High School Student - Hella Ayu Setyanida (Universitas PGRI Semarang, 2019)
ThisstudyaimedtoanswerhowmuchQuippergiveadvantagesasthemediaforteaching EnglishinJuniorHighSchoolandhowQuipperApplicationworkasthemediaforteaching EnglishinJuniorHighSchool.ThisresearchwasconductedatSMPN1Kaliwunguwhich waslocatedonJalanPangeranDjuminah51372KaliwunguSelatanKendal.Theresearch wasconductedonSeptember2017.Thisresearchuseddescriptivestudy.Theresearcherused descriptivemethodbecauseitdescribedresultofusingQuipperasmediaforEnglish TeachinginJuniorHighSchool.Theresearchdatainthisstudyconsistsofsomesources informationfromusingQuipperSchoolinSMPN1Kaliwungu.Thesampleofthisresearch was5studentsfromSMPN1Kaliwungu,theywereinsecondlevelofJuniorHighSchool and also weinterviewed1 English Teacher from SMPN 1 Kaliwungu.Theresult of this paper wastheadvantage ofusingQuipper SchoolinEnglishclassroom.Theyusedablendedonline course thatgatheredbothteachersandstudentsinaclassroomwithadditionalvirtuallearning viaQuipperSchool.Theconventionalface-to-faceteachinglearningwasalsoequippedby the useof theinternet to make itmore attractive and interesting